Instantaneous death risk, conditional survival and optimal surgery timing in cervical fracture patients with ankylosing spondylitis: A national multicentre retrospective study - Huang, Jinfeng; Bai, Hao; Tan, Quanchang; Hao, Dingjun; Wu, Aimin; Wang, Qingde; Wang, Bing; Wang, Linfeng; Liu, Hao; Chen, Xiongsheng; Jiang, Zhengsong; Ma, Xiaoming; et al. (Frontiers in Immunology, 2022)
Background The mortality rate in patients with ankylosing spondylitis (AS) and cervical fracture is relatively high. Objectives This study aimed to investigate the instantaneous death risk and conditional survival (CS) in patients with AS and cervical fracture. We also studied the relationship between surgical timing and the incidence of complications. Methods This national multicentre retrospective study included 459 patients with AS and cervical fractures between 2003 and 2019. The hazard function was used to determine the risk of instantaneous death. The five-year CS was calculated to show the dynamic changes in prognosis. Results The instantaneous death risk was relatively high in the first 6 months and gradually decreased over time in patients with AS and cervical fracture. For patients who did not undergo surgery, the instantaneous risk of death was relatively high in the first 15 months and gradually decreased over time. For patients with American Spinal Injury Association impairment scale (ASIA) A and B, the 5-year CS was 55.3% at baseline, and improved steadily to 88.4% at 2 years. Odds ratios (ORs) for pneumonia, electrolyte disturbance, respiratory insufficiency, and phlebothrombosis decreased as the surgery timing increased. Conclusion Deaths occurred mainly in the first 6 months after injury and gradually decreased over time. Our study highlights the need for continued surveillance and care in patients with AS with cervical fractures and provides useful survival estimates for both surgeons and patients. We also observed that early surgery can significantly increase functional recovery, and decrease the incidence of complications and rehospitalisation.